PENGARUH TINGKAT PENDAPATAN ORANG TUA TERHADAP KEINGINAN PESERTA DIDIK MELANJUTKAN KE PERGURUAN TINGGI - Sukmawati, Linda; Aminuyati, Aminuyati; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Education is a learning experience and the knowledge gained in a school environment lasts throughout life. From the beginning, education plays a role in deciding students' desires to continue to higher education with encouragement and desires from students and the surrounding environment. From this desire arises their interest in continuing their higher education so that they are interested in continuing an education that is higher than their previous education. This research aims to determine the level of parental income regarding students' desire to go to college at Islamic High School Bawari Pontianak. The type and design of this research is quantitative descriptive. The results of the research show that there is a positive and significant influence between parents' income on interest in continuing their studies at tertiary level. Parental income in increasing students' interest in continuing their education to college was 10.3% while the remaining 89.7% was influenced by other variables. The results of this research show that there is a positive and significant influence between parents' income on the desire to continue their studies at tertiary level.